Possibility of clove oil usage in chicken coccidiosis therapy - Novaković Zorica; Mekić Cvijan; Novaković Branka (Agroznanje, 2011)
In intensive broiler production because of high number of chicken per m2 of flooring danger of quick disease spreading is present. If adequate zoohygienical conditions are not provided, proper feeding as well as application of specific medications which are added in feed mix there is high risk of different deseases appearance and most common one is coccidiosis. This assay shows results of clove oil usage compared with coccidiosis medication coccidiostatic called "Cygro" which is being used in feed mixes for broiler fattening. To check the effect of clove oil in stopping the appearance of coccidiosis four experimental chicken groups were formed: I group was control group without application of any coccidiostatic; P group had feed mix with "Cygro" medicament; III group had feed mix with 0,2% of clove oil, and Š group got clove oil in drinking water in concentration of 0,2%. Research has shown that effect of clove oil application in water and feed mix had same effect as application of "Cygro" medicament. Moreover the mortality of chicken within control group was 70%; P group 13,33%; III group 13,33% and Š group 16,67%. Based on above results we can conclude that it is necessary to apply some coccidiostatic to prevent the appearance of coccidiosis in broiler fattening industry, and that usage of natural medicament such as clove oil compared to sinthetical medicament "Cygro" is justified as same results were achieved.